Hubungan Usia dan Status Menopause dengan Kejadian Bacterial Vaginosis pada Pasien Keputihan - Budhi, Dono Setya; Wahyudi, Didik (Department of Health Analyst, Politeknik Kesehatan, Kementerian Kesehatan Tanjungkarang, 2023)
Bacterial Vaginosis (BV) is a condition of imbalance in the vaginal ecosystem, namely decreased number Lactobacillus followed by an increase in numbers Gardnerella vaginalis and other anaerobic bacteria. About 90% of Indonesian women have the potential to experience vaginal discharge because Indonesia has a tropical climate and the incidence continues to increase every year up to 70%. The purpose of this research was to determine the correlation between age and menopausal status with the incidence bacterial vaginosis in vaginal patients. This research method is observational analytic, looking at the correlation between age and menopausal status with incidence bacterial vaginosis in vaginal patients. The number of samples used was 28 patients. Diagnosis bacterial vaginosis was carried out using the Gram staining method then a nugent scoring system was carried out by adding up the three morphological forms of bacteria found (large-sized Gram-positive rods, small-sized Gram-variable rods and bent Gram-negative rods/Gram-variable rods). Data analysis used fisher's exact test. Based on the results of the research, the prevalence of positive BV was 67.9% with the most characteristics of patients aged over 51 years at 90.9%, menopause at 90.9%. The fisher's exact test analysis showed a p-value for age = 0.020 (p